Distribution pattern of planktonic and benthic foraminifera in surface sediments near the equatorial western Indian Ocean and its indications of paleo-environment and productivity. (1st July 2023) - Shen, Wei; Qiao, Shuqing; Sun, Rongtao; He, Zhoutian; Wu, Bin; Jin, Lina; Chen, Liang; Yin, Zhengxin; Ge, Chendong; Shi, Xuefa; Sheng, Jie
Highlights: The distribution of planktonic foraminifera was mainly influenced by the depth-controlled dissolution rate of carbonate, temperature, and salinity. Strong correlations were found between the benthic foraminiferal distribution and organic carbon, the oxygen content, and the water mass. Benthic foraminifera assemblage of Cibicidoides wuellerstorfi and Oridorsalis umbonatus indicated the influence and direction of oxygen-rich Antarctic Bottom Water. The carbonate lysocline depth of the equatorial western Indian Ocean is ∼ 3900 m. The western side of the Central Indian Ridge is relatively more productive than the eastern region, which reflects the influence of Seychelles-Chagos Thermocline Ridge. Abstract: The numerous foraminifera in sediments near the equatorial western Indian Ocean act as historiographers that record abundant information about the marine environment. However, few studies have focused on the foraminiferal distribution in surface sediments within this area and the associated environmental and productivity implications. In this study, planktonic and benthic foraminifera were obtained from 28 surface sediments. The planktonic foraminifera were found to be mainly warm-water species; their distribution was mainly influenced by depth-controlled dissolution rate of carbonate, temperature, and salinity. Combined vertical distribution of foraminifera, fragment rate, resistant species rate, and Goborotalia menardii fragmentation index, the carbonate lysocline depth of the equatorial western Indian Ocean is ∼ 3900 m. The benthic foraminifera were mostly oxygen-rich and oligotrophic species. Their distribution and organic carbon, the oxygen content, and the water mass related. Four assemblages were identified: Assemblage 1, Cibicidoides wuellerstorfi, Oridorsalis umbonatus [indicative of Antarctic Bottom Water (AABW)]; Assemblage 2, Pullenia bulloides, Oridorsalis umbonatus (indicative of an oxygen-rich environment with intermediate to low productivity); Assemblage 3, Epistominella exigua, Turrilina cf. brevispira (indicating a pulsed organic matter input and seasonal fluctuations in productivity); Assemblage 4, Globocassidulina subglobosa, Astrononion novozealandicum (suggestive of a low-productivity environment). The overall productivity is low near the equatorial western Indian Ocean. The foraminifera species, TOC, and biogenic barium data show that the western side of the Central Indian Ridge is relatively more productive than the eastern region. These results can be used as a basis for reconstructing the distribution of paleo-AABW and productivity within the Indian Ocean.